The Evaluation of Surrogacy’s System in Indonesia as Comparison to India’s Legislation - Ambarwati, Mega Dewi; Azmita Kamila, Ghina (University of Jember, 2019)
In today’s age, marriage life is can be complicated with problems like infertility. In the face of this problem, couples have used surrogacy as a potential fix. Surrogacy poses a unique problem in Indonesia, because such a concept remains culturally taboo and no legal system exists to regulate the process and the responsibilities of the surrogate mother. Thus, other countries that have created a legal infrastructure for surrogacy offer valuable paradigms and best practices. This study seeks to compare surrogacy law between Indonesia and India, with the overall goal of suggesting policies to better regulate surrogacy within the former country. This study uses comparative legal research methodology through the functional method because Indonesia and India face the same social problem of surrogacy. The result reveals that it needs a legal system on surrogacy and surrogate mother as the legal certainty for any individual especially spouse who could not have offspring along with some reasons such as minimalize prostitution and unregistered marriage, prevent dispute, and to develop scientific field. The study concludes that Indonesia requires stronger legal infrastructure for surrogacy that will not only provide legal certainty for surrogate mothers and families using surrogacy but will also minimize prostitution and unregistered marriages, mitigate domestic disputes, and catalyze scientific innovation. Keywords: Surrogate Mother, Surrogacy, Indonesia, India.